Avaliação de diferentes agentes clarificantes no fermentado de arroz para a produção de saquê - Soares de Almeida, Camila (Universidade Federal de São Carlos, 2022)
Rice can be used in the alcoholic fermentation process, which combines the saccharification of the grain (transformation of starch into sugar), the use of a filamentous fungus of the Aspergillus species and the reaction of transformation of sugar into alcohol by the yeast Saccharomyces cerevisiae. Clarification is an operation that aims to eliminate all substances, in suspension or dissolution, existing in a liquid, to make it clear and crystalline. One of the methods used for clarification is the use of bentonite, which acts through electrostatic charges. Other alternatives are the use of gelatin, which has been widely used in the clarification of beverages for its effective precipitation of agents such as tannin, due to its ability to form insoluble complexes with proteins, and the use of carrageenan gum, which has the ability to maintain particles in suspension and electrostatic connection. Therefore, the objective of this work was to obtain an alcoholic fermented product from rice wort and to test the use of different types of clarifying agents such as bentonite clay, associated bentonite and gelatin and carrageenan gum. The results were analyzed in terms of their physicochemical characteristics, and all parameters were in accordance with current legislation for sake production. Bentonite associated with gelatin was the clarifying agent that obtained the most satisfactory result, with turbidity values of 11.2 NTU, which can be concluded that its use is viable as a clarifying agent and in the reduction of turbidity and absorbance.
Evaluation of different clarifying agents in sake production
Keywords: Fermentação; Arroz; Clarificação; Bentonita; Gelatina; Goma carragena; Fermentation; Rice; Clarification; Bentonite; Gelatin; Carrageenan Gum; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::ENGENHARIA DE ALIMENTOS::INSTALACOES INDUSTRIAIS DE PRODUCAO DE ALIMENTOS